1987
DOI: 10.1002/1097-0142(19871215)60:12<2994::aid-cncr2820601223>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow magnetic resonance studies in childhood leukemia. Evaluation of osteonecrosis

Abstract: In 25 patients under treatment or during follow-up for acute lymphoblastic leukemia magnetic resonance imaging (MRI) of both knees was compared to history and physical examination to detect osteonecrosis. Results of MRI were classified as: 0, normal bone marrow (BM); 1, diffuse decrease in signal intensity; 2, circumscript lesions. Patients clinically suspected of osteonecrosis had a statistically significant increased incidence of Type 2 lesions. Three patients with a BM relapse also showed Type 2 lesions. Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 46 publications
0
14
1
2
Order By: Relevance
“…In the early stages, patients are treated with nonweight-bearing activities such as swimming to maintain joint function and to control body weight. 14,49 At more advanced stages, surgical intervention (ie core decompression, arthroplasty, or total joint replacement) may be necessary to ameliorate symptoms and preserve joint function. 14,49 Using multivariate analysis, investigators at the University of Minnesota identified increasing age at the time of BMT (P ¼ 0.002), acute or chronic GVHD requiring steroid therapy (P ¼ 0.003) as significant and independent risk factors for developing osteonecrosis after allogeneic transplantation in 28 (4%) of 642 consecutive patients ranging in age from 1.5 to 47 years (median, 26 years) at the time of BMT.…”
Section: Osteonecrosismentioning
confidence: 99%
“…In the early stages, patients are treated with nonweight-bearing activities such as swimming to maintain joint function and to control body weight. 14,49 At more advanced stages, surgical intervention (ie core decompression, arthroplasty, or total joint replacement) may be necessary to ameliorate symptoms and preserve joint function. 14,49 Using multivariate analysis, investigators at the University of Minnesota identified increasing age at the time of BMT (P ¼ 0.002), acute or chronic GVHD requiring steroid therapy (P ¼ 0.003) as significant and independent risk factors for developing osteonecrosis after allogeneic transplantation in 28 (4%) of 642 consecutive patients ranging in age from 1.5 to 47 years (median, 26 years) at the time of BMT.…”
Section: Osteonecrosismentioning
confidence: 99%
“…Harper et al published work in the 1980s suggesting that chemotherapy agents alone may be responsible in the pathophysiology of avascular necrosis of the femoral head, amongst other sites. 4 Several studies have linked osteonecrosis to the UKALL treatment regime for ALL, [5][6][7][8] which was used in this case. Is it possible that the SCFE occurred due to an iatrogenic shift of physeal physiology at an age where the physis widens and periosteum thins 9 within 3 weeks following chemosteroidal treatment, both of which being implicated in the literature in the pathogenesis of ON.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 From here on, we refer to symptomatic osteonecrosis as ON. ON was graded according to the National Cancer Institute (NCI) Common Terminology criteria for Adverse Events, version 3.0.…”
Section: Osteonecrosismentioning
confidence: 99%